Riociguat treatment in patients with chronic thromboembolic pulmonary hypertension: Final safety data from the EXPERT registry. (March 2021) - Ghofrani, Hossein-Ardeschir; Gomez Sanchez, Miguel-Angel; Humbert, Marc; Pittrow, David; Simonneau, Gérald; Gall, Henning; Grünig, Ekkehard; Klose, Hans; Halank, Michael; Langleben, David; Snijder, Repke J.; Escribano Subias, Pilar; et al.
Abstract: Objective: The soluble guanylate cyclase stimulator riociguat is approved for the treatment of adult patients with pulmonary arterial hypertension (PAH) and inoperable or persistent/recurrent chronic thromboembolic pulmonary hypertension (CTEPH) following Phase 3 randomized trials. The EXPosurE Registry RiociguaT in patients with pulmonary hypertension (EXPERT) study was designed to monitor the long-term safety of riociguat in clinical practice. Methods: EXPERT was an international, multicenter, prospective, uncontrolled, non-interventional cohort study of patients treated with riociguat. Patients were followed for at least 1 year and up to 4 years from enrollment or until 30 days after stopping riociguat treatment. Primary safety outcomes were adverse events (AEs) and serious adverse events (SAEs) coded using Medical Dictionary for Regulatory Activities preferred terms and System Organ Classes version 21.0, collected during routine clinic visits and collated via case report forms. Results: In total, 956 patients with CTEPH were included in the analysis. The most common AEs in these patients were peripheral edema/edema (11.7%), dizziness (7.5%), right ventricular (RV)/cardiac failure (7.7%), and pneumonia (5.0%). The most common SAEs were RV/cardiac failure (7.4%), pneumonia (4.1%), dyspnea (3.6%), and syncope (2.5%). Exposure-adjusted rates of hemoptysis/pulmonary hemorrhage and hypotension were low and comparable to those in the long-term extension study of riociguat (Chronic Thromboembolic Pulmonary Hypertension Soluble Guanylate Cyclase–Stimulator Trial [CHEST-2]). Conclusion: Data from EXPERT show that in patients with CTEPH, the safety of riociguat in routine practice was consistent with the known safety profile of the drug, and no new safety concerns were identified. Highlights: Riociguat is approved for treatment of chronic thromboembolic pulmonary hypertension (CTEPH). The EXPERT study evaluated the safety of riociguat in clinical practice. Results are available for 956 CTEPH patients in 28 countries, followed for 1–4 years. The safety of riociguat in clinical practice was consistent with clinical trials. No new safety concerns were identified.